Blumgart versus conventional anastomosis for pancreatojejunostomy after pancreaticoduodenectomy - What will we choose? - Saha, Haridas; Ansary, Abdullah Md Abu Ayub; Rahman, Md Mostafizur; Arifuzzaman, Md; Alam, Shoaeb Imtiaz; Rahman, Atiar; Chowdhury, Mohammad Imrul Hasan; Shahriar, Shaon (Journal of Surgical Sciences, 2025)
Background: Pancreatic leakage is a major cause of postoperative mortality and morbidity after pancreaticoduodenectomy (PD). A recent study introduced Blumgart anastomosis (BA), which minimizes severe complications after PD. This study compares BA with conventional anastomosis (CA) for pancreaticojejunostomy (PJ) after PD in the Department of Surgical Gastroenterology, Sheikh Russel National Gastroliver Institute and Hospital. Methods: This retrospective observational study includes 20 patients who underwent PD between November 2020 to November 2021. The patients were divided into two groups according to the anastomosis type. Of them, 10 patients underwent anastomosis using CA (group A, conventional anastomosis including Dunking and Duct to mucosa) and 10 underwent anastomosis using BA (group B, Blumgart anastomosis). The methods were compared in context of postoperative pancreatic fistula (POPF), post pancreatectomy hemorrhage (PPH), and delayed gastric emptying (DGE) to see the overall outcome of two techniques. Results: Mean duration of operation time was significantly shorter in group B (373.1±102.0 versus 256.4±58.5 min, p<.05), and the number of intraoperative transfusion units (mean) was less in group B (2.5±1.4 versus 1.7±1.5 unit). Statistically significant difference was also observed between groups A and B in the incidence of postoperative pancreatic fistula (POPF) (30.0% versus 10.0%, p=034.) and PPH (50% versus 30%, P=0.0643), DGE (30% versus 40%, p=0.124) was not statistically significant. The length of postoperative hospital stay (mean) was not statistically different between groups A and B (12.0±6.3 versus 10±7.2 days, p=0.08). There was one mortality which was observed in Group-A. Conclusions: BA after PD was associated with a decreased risk POPF, DGE and PPH. Therefore, the results of this study suggest that BA-type PJ is superior to CA-type PJ in terms of postoperative complications. Journal of Surgical Sciences (2021) Vol. 25 (1) : 47-52